Toppling the Taliban Air-Ground Operations in Afghanistan, October 2001-June 2002 - Perry, Walter L. (Research Reports, 2015)
On September 11, 2001, the United States was without a plan for military operations in Afghanistan. One was quickly created by the Defense Department and operations began October 7. The Taliban was toppled in less than two months. This report describes preparations at CENTCOM and elsewhere, Army operations and support activities, building a coalition, and civil-military operations in Afghanistan from October 2001 through June 2002.